The Relationship Between Expectation Regarding Aging and Functional Health Status Among Older Adults in China. Issue 4 (22nd May 2013) - Li, Xianwen; Lv, Qiyuan; Li, Chunyu; Zhang, Hailian; Li, Caifu; Jin, Jinzhen
Abstract Purpose To examine the level of and factors influencing expectations regarding aging (ERA) among older Chinese adults, and to determine whether leisure‐time exercise mediates the association between ERA and functional health status. Methods A population‐based, cross‐sectional design was utilized in this study. A total of 550 participants completed the face‐to‐face interview via a questionnaire addressing ERA, physical health conditions, personality and psychological factors, leisure‐time exercise, and functional health status. Results More than four fifths of the older adults felt that having more aches and pains (88.0%), lower levels of energy (82.7%), and being forgetful (82.5%) were an accepted part of aging, and 74.7% of participants reported it to be true that "being depressed is normal for older adults." The regression model showed that depression and self‐mastery were factors that influence ERA among older Chinese adults (β = −0.26, p = .000; β = 0.15, p = .000). The Instrument Activity of Daily Life and World Health Organization Disability Assessment scores were not associated with ERA. Leisure‐time exercise mediated the relationship between ERA and functional health status. Conclusions Older adults generally consider body function decline to be an expected part of aging. Personality and psychological factors, rather than physical health conditions, were the factors that were considered to be most influential on ERA among Chinese older adults. These findings suggest that community interventions taking into account leisure‐time exercise could be influential in improving the ERA and functional health status of older adults. Clinical Relevance For community nurses and other primary care providers, the findings of the present study may facilitate the subsequent design of community‐based participatory intervention to improve ERA, as well as potentially improve the functional health status of older adults.